The wedding letters : a novel - Wright, Jason F. (Shadow Mountain, 2011)
Noah is preparing to marry Rachel. However, when a dark secret from Rachel's past surfaces, Noah and his parents, Malcolm and Rain, must find a way to heal Rachel's heart as well as save the wedding. Perhaps a scrapbook of wedding letters filled with good wishes and marriage advice will hold the key the couple needs to find love and happiness.